Estudio de prefactibilidad para la instalación de una planta procesadora de desinfectante concentrado en cápsulas - Garcia Urure, Diana Nicolle (2022)
The year 2020 meant an abysmal change for all the nations of the world, the resounding arrival and proliferation of the SARS-CoV-2 virus has brought with it many consequences, including the evolution of consumer habits that has gradually turned to adopt habits of cleaning and hygiene more sophisticated and serious. The personal and home care industry has benefited from these changes and this present opportunity represents the raising and a potential positive reception of products with great disinfecting power. In the present research work, the aim is to take advantage of this opportunity through a pre-feasibility study for the installation of a processing plant for concentrated disinfectant in capsules. The market study was carried out in the Metropolitan Lima region, where with the help of a survey of 385 people, indicators of purchase intention (98%) and intensity (77,09%) were determined. The target market was determined in all the people of Metropolitan Lima and Callao of the socioeconomic levels A and D, to ages of 33 to more years. The decision was to locate the 648 m2 production plant in the district of Lurín, because of an analysis of the impact of multiple suitable factors such as nearness to distribution centers and raw material. Regarding the production technology, the process will contemplate the stages of reception - mixing - rest and quality control - encapsulation - boxing and labeling; with a production capacity of 307 806 boxes of disinfectant per year. Finally, the costing of operations determined an initial investment of S/ 2 141 224 for the implementation, which is made up of 60% by equity capital and 40% in financing at increasing rates by the BBVA bank. In addition, the financial indicators NPV and TIR amount to S/ 716 412 and 32,0% respectively, reaching the conclusion that the project is financially and economically viable.